2019
DOI: 10.13031/jash.13165
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Agricultural Injuries in Pennsylvania, 2015-2017: A Comparative Analysis of Two Systems’ Data Collection Methods and Datasets

Abstract: tified in Pennsylvania across both systems. Differences between the two systems included coding, such as victim age and demographics, as well as inclusion criteria, such as the time between the incident and victim death. Of the 104 agricultural fatalities, 73% were identified through the PA-FF dataset, and 53% were identified through the AIN dataset. AIN included a higher proportion of female victims and roadway incidents, whereas PA-FF included a significantly higher proportion of the identified Anabaptist ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Perhaps most notably, media reports do not always collect enough detail, do not cover all AFF fatalities, and cover even fewer stories relating to AFF nonfatal injuries. There are also some gaps in collection efforts, and there is room for improvement in interagency collaborations, a topic of future research [56]. In addition, previous studies have identified a discrepancy in the number of drowning fatalities among youth as being poorly captured by news media [25].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps most notably, media reports do not always collect enough detail, do not cover all AFF fatalities, and cover even fewer stories relating to AFF nonfatal injuries. There are also some gaps in collection efforts, and there is room for improvement in interagency collaborations, a topic of future research [56]. In addition, previous studies have identified a discrepancy in the number of drowning fatalities among youth as being poorly captured by news media [25].…”
Section: Discussionmentioning
confidence: 99%
“…(1) building new emphases on improved coding systems [11]; (2) enhanced collaborative efforts with partners and government datasets [12]; and (3) exploring injuries in vulnerable, underrepresented populations, such as youth [13][14][15]. The AgInjuryNews system collects news media reports from news agencies across the United States and Canada and codes them based on multiple factors, including: injury agent, incident location, Farm and Agricultural Injury Classification (FAIC) codes, victim demographics, and more [16].…”
Section: Introductionmentioning
confidence: 99%